Podmiotowość nauczyciela polonisty - Worsowicz, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The article contains discussion about the most important aspects of subject attitude in teaching of Polish language. The analysis of conditions of perception a student as a subject indicates that a teacher of Polish language needs high qualifications. Broad knowledge and good discernment in a psychological and social interactions between a student and him let the teacher respect individuality of his pupil and enrich consciousness of both of them. Frankness for subject understanding for the fact that they are two separate subjects obligates the teacher to professional creativity and though improvement can come across the various obstacles, it should be a stable element of didactic process. The theses represented lead to the conclusion that subjectivity is the way to create relationships among other people, which is coming not only from particular way of thinking but also from internal need based on system of values and deep sense of ties with others. The realisation of subjectivity is teaching how to be an individual in one community.